HUBUNGAN KEMAMPUAN LITERASI SAINS DENGAN KEMAMPUAN LITERASI DIGITAL PESERTA DIDIK KELAS V SDN CENGKARENG BARAT 03 PAGI - Muhammad Ali; Budhi Akbar (PIONIR: JURNAL PENDIDIKAN, 2023)
The purpose of this study was to analyze the relationship between scientific literacy skills and digital literacy skills of fifth grade students at SDN Cengkareng Barat 03 Pagi. The method used in this research is descriptive correlational with moment product correlation test. Researchers collected data through tests for scientific literacy and questionnaires for digital literacy. The results showed that out of 60 students, the highest score of Scientific Literacy was 90 and the lowest score was 65 with Minimum Completeness Criteria (KKM) of 75. The normality test shows that the significance value of scientific literacy and digital literacy is greater than 0.05 (0.200 > 0. 05, 0.200 > 0.05 and 0.132 > 0.05, 0.200 > 0.05). The result of the linearity test is that the significance value is greater than 0.05 (0.631 > 0.05). Based on the results of this study, it can be concluded that there is a relationship between scientific literacy skills and digital literacy abilities of fifth grade students at SDN Cengkareng Barat 03 Pagi in the high category with a value of r = 0.691.